2020
DOI: 10.21203/rs.3.rs-130173/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-inflammatory diet consumption reduced fatty liver indices:  Finding from a large cohort study in the Kurdish population

Abstract: Background The aim of this study was the assess association between of dietary inflammatory index (DII) and non-invasive markers of liver status in adults. Methods This cross-sectional study was performed on 8,520 individuals aged 35–65 years, recruited in Ravansar Non-Communicable Diseases (RaNCD) cohort study, the west of Iran. DII score was calculated based on participants’ dietary intakes obtained from Food Frequency Questionnaire (FFQ). Fatty Liver Index (FLI) score was calculated by anthropometric meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(47 reference statements)
0
2
1
Order By: Relevance
“…In terms of markers of liver function, positive associations between the AE-DII, GGT, ALT and AST were observed. As opposed to prior observations (49,50) , the AE-DII was not associated with increased GGT, AST and ALT levels in the PURE-NWP-SA population through the pathway of obesity/fatty liver disease, as the associations remained after adjustment. Instead the associations appear, at least in part, to be related to alcohol consumption, as adjustment therefore nullified the association between the AE-DII and the liver enzymes.…”
Section: Ae-dii In the Pure-nwp-sa Cohort: The Role Of Urbanicitycontrasting
confidence: 99%
“…In terms of markers of liver function, positive associations between the AE-DII, GGT, ALT and AST were observed. As opposed to prior observations (49,50) , the AE-DII was not associated with increased GGT, AST and ALT levels in the PURE-NWP-SA population through the pathway of obesity/fatty liver disease, as the associations remained after adjustment. Instead the associations appear, at least in part, to be related to alcohol consumption, as adjustment therefore nullified the association between the AE-DII and the liver enzymes.…”
Section: Ae-dii In the Pure-nwp-sa Cohort: The Role Of Urbanicitycontrasting
confidence: 99%
“…In the AID group, there was a significant decrease in ALP levels. Darbandi et al ( 2020 ) have shown that adherence to an AID is associated with lower liver enzymes, including AST, ALT, and GGT. It seems that weight loss inhibits the accumulation of lipid in hepatocytes, resulting in a reduction of inflammatory response via NF‐κB activation and cytokine production, which leads to a decrease in liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Darbandi et al (2020) have shown that adherence to an AID isTA B L E 5Abbreviations: AID, anti-inflammatory diet; G, ginger; GPA, ginger plus anti-inflammatory diet.…”
mentioning
confidence: 99%